Comparative real-world effectiveness of vedolizumab and ustekinumab for patients with ulcerative colitis: a GETAID multicentre cohort study. (2nd December 2022) - Meyer, Antoine; Fumery, Mathurin; Peyrin-Biroulet, Laurent; Filippi, Jérôme; Altwegg, Romain; Bouhnik, Yoram; Serrero, Melanie; Laharie, David; Roblin, Xavier; Nachury, Maria; Abitbol, Vered; Cadiot, Guillaume; et al.
Abstract: Introduction: There are currently no comparative data on the efficacy and safety of vedolizumab and ustekinumab in ulcerative colitis (UC) after anti-TNF therapy fails. Methods: We retrieved the full datasets of two observational, multicentre, retrospective studies of patients with UC for whom anti-TNF therapy failed and the patients were then treated with either vedolizumab or ustekinumab. The outcomes included steroid-free clinical remission, clinical remission, treatment persistence, colectomy, hospitalization, and serious and infectious adverse events. Propensity scores weighted comparison was applied. Results: In total, 121 patients were included in the vedolizumab group and 97 were included in the ustekinumab group. At week 14 and week 52, in the weighted cohort, no difference was found between vedolizumab and ustekinumab for steroid-free clinical remission (OR = 0.55 [0.21–1.41], p = .21 and 0.94 [0.40–2.22], p = .89, respectively). There was no difference between vedolizumab and ustekinumab for secondary outcomes such as clinical remission, hospitalization, UC-related surgery, treatment persistence and serious and infectious adverse events. Conclusion: In patients with UC for whom anti-TNF therapy failed, no difference was found between vedolizumab and ustekinumab after propensity scores weighted comparison. Further studies are required to determine predictive factors of the efficacy of both biological agents.